An Examination of the Effects of 2M Channel Airing Turkish Soap Operas on Moroccan Audiences: 2009-2019 (American Journal of Arts and Human Science, 2024)
This paper attempts to shed light on the media effects of the 2M channel on Moroccan audiences viewing dubbed Turkish soap operas (TSO). In particular, the study limits its scope to 2009-2019 period of broadcasting. It is noted that the viewing process is a prerequisite for social change and media effects. This consideration of direct exposure hastens the effects and influences in the audiences’ lives. Not all media effects of TSO are detrimental to the Moroccan audience and government. No sooner had the audience finished a dubbed Turkish serial than the 2M started broadcasting a new one. Additionally, to examine this decade, the paper invests structured interviews and mail surveys to collect data. The study treats the research findings with content analysis and discourse analysis. Presumably, it is noticeable that females are the majority of viewers. Accordingly, the research findings are manifold. The study’s research findings seriously alert the media analysts and Moroccan cultural authorities concerned with Moroccan audiences susceptible to the TSO increasing dangers and insidious menaces. These foreign influences are disseminated through the ignorance, recipient, and Moroccan female lifestyles. Therefore, the result discussion necessitates an awakening paradigm shift in Moroccan cultural policy. In conclusion, the paper calls for an invigorating Moroccan public screen. Moroccan soap opera alternative likely replaces Turkish soap opera since Moroccan audience counts in millions alongside religious diplomacy as a form of soft power.